Unilateral Acute Parotitis: A Novel Manifestation of Pediatric Coronavirus Disease - Sushil Sharma; Vikas Mahajan; Ravinder Gupta (Wolters Kluwer Medknow Publications, 2022)
Background: Severe acute respiratory virus coronavirus-2 infection or coronavirus disease (COVID) is categorized into acute illness and late multiinflammatory syndrome in children (MISC). This has recently been challenged with recognition of presentations with mucocutaneous-enteric symptoms that display considerable overlap between the two. We recognized a similar overlap of manifestations when encountered the three cases of fever associated with unilateral parotitis. Clinical Description: The three patients were of different age groups ranging from 2 months to 7 years of age, all of whom presented with fever, unilateral swelling of face and neck consistent with the region of the parotid gland, and absence of other localizing symptoms or abnormalities on examination. All of them were positive for COVID antibodies, had negative COVID real-time polymerase chain reaction test, did not satisfy the diagnostic criteria of MISC, but had raised inflammatory markers. Since the workup for other common causes of acute parotitis was negative, a clinical diagnosis of post-COVID immune-mediated acute parotitis was kept. Management: All the three patients were managed with systemic steroids (oral or parenteral) and showed complete resolution of symptoms and normalization of laboratory parameters within a few days, a therapeutic response in alignment with an immune-mediated phenomenon. Conclusion: Acute unilateral parotitis with pyrexia may be a hitherto unreported late post-COVID manifestation that is immune mediated and shows an excellent therapeutic response to a short course of steroids.